Jatrophane and lathyrane diterpenoids from Euphorbia hyberna L - Ferreira, Ana Margarida V. D. (2022)
A new diterpene tetraester, from the jatrophane family, and two new diterpene triesters, with a lathyrane skeleton, have been isolated from the chloroform extract of the roots of Euphorbia hyberna L. The structures of these compounds have been established by spectroscopic methods, including 2D NMR experiments.